2014
DOI: 10.5604/20831862.1111436
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Exercise Arginine Supplementation Increases Time to Exhaustion in Elite Male Wrestlers

Abstract: Dietary supplements containing arginine are among the most popular ergogenics intended to enhance strength, power and muscle recovery associated with both anaerobic and aerobic exercise. The aim of the present study was to evaluate the possible effect of pre-exercise acute intake of arginine on performance and exercise metabolism during incremental exhaustive exercise in elite male wrestlers. Nine volunteer elite male wrestlers (24.7±3.8 years) participated in this study. The test-retest protocol was used on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 26 publications
2
32
1
Order By: Relevance
“…A meta-analysis of randomized, double-blind, placebo-controlled trials showed that oral l -arginine significantly lowered systolic and diastolic blood pressure compared with placebo [6]. In addition to demonstrated benefits in patients, arginine supplementation has been shown to enhance exercise performance in athletes and active adults through an increased time to exhaustion [7], improved recovery [8], and delayed muscular fatigue [6,9]. In healthy, minimally active males (19–33 years of age), ASI supplementation (1500 mg/day) for 4 days significantly increased pre-workout energy levels, increased muscle hyperemia, or measured size, over baseline measured by upper leg circumference post-exercise, and reduced biomarkers of muscle damage during recovery from exercise, supporting its role as a sports nutrition ingredient [10].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of randomized, double-blind, placebo-controlled trials showed that oral l -arginine significantly lowered systolic and diastolic blood pressure compared with placebo [6]. In addition to demonstrated benefits in patients, arginine supplementation has been shown to enhance exercise performance in athletes and active adults through an increased time to exhaustion [7], improved recovery [8], and delayed muscular fatigue [6,9]. In healthy, minimally active males (19–33 years of age), ASI supplementation (1500 mg/day) for 4 days significantly increased pre-workout energy levels, increased muscle hyperemia, or measured size, over baseline measured by upper leg circumference post-exercise, and reduced biomarkers of muscle damage during recovery from exercise, supporting its role as a sports nutrition ingredient [10].…”
Section: Introductionmentioning
confidence: 99%
“…There is also some evidence that ARG supplementation could have a beneficial influence on anaerobic capacity. Yavuz et al (9) examined the significance of a single dose of L-arginine (1.5 g •10 kg -1 body weight) given to 9 male national and international level wrestlers after a 12-hour (night) fast. The athletes performed an incremental bicycle ergometer test to exhaustion during which several parameters (oxygen consumption, heart rate and plasma lactate levels)…”
Section: Introductionmentioning
confidence: 99%
“…Amino acids are among the most common nutritional supplements used by athletes and recreationally active adults to improve physical performance and muscle recovery (Yavuz et al 2014). In particular, an over-the-counter supplement called L-arginine (L-arg) has received special attention in last two decades due to its probable ergogenic effects (Àlvares et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the aforementioned mechanisms, it is postulated that L-arg supplementation may improve muscle performance and recovery by increasing nutrients and oxygen delivery to the active muscles, improving clearance of waste-product, and increasing rate of protein synthesis. Despite an abundance of studies on physiological properties and ergogenic effects of L-arg supplementation (Bailey et al 2010;Àlvares et al 2012b;Yavuz et al 2014), no study to date has examined whether L-arg supplementation could improve the muscle function during recovery from a session of high-intensity RE.…”
Section: Introductionmentioning
confidence: 99%